Schistosomiasis: Life Cycle, Diagnosis, and Control - Martin L. Nelwan, PhD (Elsevier, 2019)
ABSTRACT: Background: Human schistosomiasis is a parasitic disease caused by blood-worms that infect multiple organs, including the liver, intestine, bladder, and urethra. This disease may be eliminated with Praziquantel, vaccines, and gene therapy. Aims: In this review, the author describes the progress in a study of schistosomiasis that focused on the life cycle, diagnosis, and control. Methodology: The author searched the PubMed Database at NCBI for articles on schistosomiasis published between 2014 and 2018. All articles were open access and in English. Results: The life cycle of this parasites involve two hosts: snails and mammals. Manifestations of schistosomiasis can be acute or chronic. Clinical manifestations of acute schistosomiasis can include fever and headache. Symptoms of chronic infections can include dysuria and hyperplasia. Infection can occur in several sites including the bile ducts, intestine, and bladder. The different sites of infection and symptoms seen are related to which of the species involved. Five species can infect humans. The three most commons are S. haematobium, S. japonicum, and S. mansoni. Detection tools for people with schistosomiasis can include the Kato-Katz and PCR. Praziquantel is at present the only effective treatment of this disease. In the future, vaccination or gene therapy may be used. Conclusion: Kato-Katz and PCR are tools for detecting schistosomiasis on humans. Praziquantel, diagnosis, vaccines, and gene therapy are useful methods for eliminating schistosomiasis. Key words: Praziquantel, Schistosome, Schistosomula, Schistosomiasis